Case studies for dangerous dust explosions in South Korea during recent years - Pak, Seonggyu; Jung, Seongho; Roh, Changhyun; Kang, Chankyu (Sustainability (Switzerland), 2019)
Despite recent extensive research and technical development to prevent and mitigate dust explosions, processes that produce and handle combustible materials in the form of powders and dusts, either as a main product or as an undesired by-product, have become a constant dust explosion threat as they become more sophisticated and complicated. This study analyzed the characteristics of 53 dust explosions that occurred in South Korea over the last 30 years, and investigated the differences of dust explosions that happened in various countries, such as Japan, the United States, the United Kingdom, and France. In addition, case studies showed the severity of dust explosions occurring in South Korea. Through the special focus on the three most recent years of dust explosions, the causes and processes of the accidents were identified. Analyses of dust explosions in South Korea show that they were mainly caused by organic matter and metal, and, unfortunately, dust explosions occurred repeatedly during grinding, mixing, and injection of powder materials into facilities. No reported accidents occurred during the production processes of wood or paper during the last three years. Taking these characteristics into account, effective ways to prevent or mitigate dust explosions at workplaces where many dust explosions occurred were suggested.
Keywords: Dust explosions; Facility; Metal; Mitigate; Organic matter; Prevent